Genetic variations in two edible frog species (Crowned Bullfrog (Hoplobatrachus occipitalis) and African clawed frog (Xenopus muelleri)) in Ibadan, Nigeria using Allozyme markers (2021)
Attempts to determine interspecific differences in patterns of protein variation in edible frog species have been relatively few. Therefore, this study determined the genetic variation in populations of Hoplobatrachus occipitalis and Xenopus muelleri in two locations [University of Ibadan (UI) and Igbo Oloyin area (IO)] in Ibadan, Nigeria, using five allozyme loci. Eighty (80) edible frogs comprising twenty (20) live samples each of H. occipitalis and X. muelleri species from IO and UI were collected. 1ml of blood was drawn per sample via cardiac venipuncture. Plasma fractions were obtained and subjected to Cellulose Acetate Electrophoresis to determine the genetic variations at Haemoglobin (HB), Carbonic anhydrase (CA), Transferrin (TF), Albumin (AL) and Esterase (EST) loci. Test for Hardy–Weinberg Equilibrium (HWE; ), Heterozygosity [observed (Ho) and expected (He)] and Genetic differentiation (FST) were estimated. Significant deviations from HWE were observed at several loci in all the populations. Ho was higher (than He) for both populations of H. occipitalis but lower for both populations of X. muelleri. FST was 0.0559 and 0.0264 for the populations of H. occipitalis and X. muelleri, respectively. There is an indication of evolutionary forces in operation in the IO populations of H. occipitalis and X. muelleri.